Homeschooling as Alternative Education in The Era of The Covid 19 Pandemic - Muhammad Yusron; Ainun Nadlif (Nazhruna: Jurnal Pendidikan Islam, 2021)
Homeschool is a structured and systematic learning activity that was initially developed in the community with an understanding that every homeschooling learning activity is carried out at home.. This study aims to find out how to implement homeschooling learning as alternative education and to find out what factors are obstacles in homeschooling learning in the era of the covid 19 pandemic. The method used in this study is qualitative descriptive which is research that is used to describe in accordance with the reality of the situation and conditions in the field. Techniques used in data collection using interviews, observation, and documentation. The results generated from research at LPTQ Zidni Ilman Paandaan, namely homeschooling is a learning activity for a child at home in full, where the learning process is responsible for the family, and if the family is unable to guide the child, the parents will call a reliable tutor in the field and at home as the basis of his education. The constraint factors faced in learning homeschooling are certainly related to the cognition and psychosis of each child, including how to remember, make decisions, and take responsibility. Because in its implementation, each child has their own uniqueness in terms of intelligence and various learning styles.